Variations in COVID-19 Spread and Control Measures in the Palestinian Territories - Abed, Yehia; Shaheen, Amira; Abedrabbo, Ali (Frontiers in Public Health, 2021)
Palestinians are facing the epidemic while they are the only occupied country globally, with around 2 million inhabitants under siege in the Gaza Strip (GS) for the last 14 years and have no control over the health of the Palestinians in East-Jerusalem (EJ). Such catastrophic situations created a variety in the spread of the COVID-19 pandemic in different territories. This study aimed to explore variation in COVID-19 spread, risk factors, and intervention activities in the three Palestinian territories: West Bank (WB), EJ, and GS to learn from the current gaps to overcome this pandemic and be prepared for future emergencies. Epidemiological data regarding COVID-19 were obtained from online websites, Palestinian national reports, WHO reports, and scientific publications. Morbidity and mortality indicators in Palestine are higher than the global level with rate variation in the three territories. COVID-19 incidence and mortality rates are higher in EJ and lowest in GS, while case fatalities are around 1% all over the country. Social gathering and lack of readiness of the fragmented health systems (there are two systems; Palestinian serves the WB and GS and Israeli serves the EJ) are risk factors in the three Palestinian territories. The most prominent risk in GS is overcrowding, while the movement of the workers inside Israel and travel are more prevalent in the WB and EJ. The WHO and international organizations play an active role in responding to a community spread, mainly national coordination, risk communication and community engagement, laboratory support, surveillance and procurement, and supply management. Recommendations include restructuring the national committees, reviewing and standardization of the national protocols, expanding infections prevention training, supporting and developing the capacity of laboratories, and setting the role of NGOs besides community engagement and participation.